Synthesis, Characterization and Preliminary Anti-inflammatory Evaluation of New Fenoprofen Hydrazone Derivatives - Hayder M. Abdulhamza; Muthanna S. Farhan (College of Pharmacy University of Baghdad, 2020)
New hydrazone derivatives of Fenoprofen were synthesized and evaluated for their anti-inflammatory activity by means of egg white induced paw edema method. All the synthesized target compounds were characterized by FT-IR spectroscopy, 1HNMR analysis and by measure of their physical properties. The synthesis of the target compounds(H1-H4) was accomplished by multistep reaction procedures. The synthesized target compounds were show activity in reducing paw edema thickness and their anti-inflammatory effect was comparable to that of the standard (Fenoprofen) except for compound H3 which show anti-inflammatory activity higher than Fenoprofen.